The Blackwell companion to consciousness - Velmans, Max, 1942-; Schneider, Susan, 1968-; Wiley InterScience (Online service) (Malden, MA ; Oxford : Blackwell Publishing, 2007)
With fifty-five peer reviewed chapters written by the leading authors in the field, The Blackwell Companion to Consciousness is the most extensive and comprehensive survey of the study of consciousness available today.:.; Provides a variety of philosophical and scientific perspectives that create a breadth of understanding of the topic.; Topics include the origins and extent of consciousness, different consciousness experiences, such as meditation and drug-induced states, and the neuroscience of consciousness.
Problems of consciousness -- The domain of consciousness -- Some contemporary theories of consciousness -- Some major topics in the philosophy of consciousness -- Major topics in the science of consciousness.
Includes bibliographical references and indexes.
Electronic resource; title from PDF title page (viewed on Dec. 20, 2007).
Keywords: Consciousness; Bewustzijn; SCIENCE -- Cognitive Science; PSYCHOLOGY -- Cognitive Psychology; Consciousness; Bewustzijn; Electronic books